Website Design of Madurejo Sleman's Pengklik Tourist Attraction Using the Waterfall Method - Tegar Satria Iman Saputra; Muhammad Sholeh; Aji Pranoto; Renna Yanwastika Ariyana; Putri Indriani (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
Website development is one of the important strategies in promoting tourist attractions and as an effort to improve access to information for tourists. This research aims to design and develop a website for Pengklik Madurejo tourist attraction, Sleman using the Waterfall method. This method was chosen because of its systematic and structured approach. The development stages begin with a needs analysis to identify the main features required, such as tourist attraction information, photo gallery, event schedule, and reservation system. Next, at the design stage, the system architecture and user interface were designed to provide an intuitive and engaging experience for users. Implementation is done by developing front-end and back-end components according to the design that has been made. Thorough testing is done to ensure the functionality, compatibility, and security of the website before launching. The development of this tourism website aims to improve the promotion and marketing of Pengklik tourist attraction. Pengklik tourist attraction is located in Madurejo Village, Sleman. The website displays various information about tourist attractions, MSME products, and activities or events that will be held. The results show that this website makes it easier for tourists and MSME players to obtain and disseminate information, as well as support the promotion and marketing of local products. The use of the website is expected to encourage economic growth in the area and increase the reach and involvement of users.